The Effect of Employee Performance on Consumer Satisfaction at Setia Hotel, Puruk Cahu, Murung Raya - Rinto Alexandro; Tonich Uda; Fendy Hariatama H.; Uci Lestari (International Journal of Social Science and Business, 2021)
Employee performance basically has a big influence on the company's contribution in terms of the quality of service provided to consumers. Employee performance is one of the main assets that must be owned by the company, especially the hotel business where the aim is to measure customer satisfaction. Quality performance will create comfort and satisfaction for consumers. But the fact is that often the problem in the field is the opposite. This study aims to analyze the influence of employee performance on customer satisfaction at Hotel Setia Puruk Cahu Murung Raya. The type and research approach used is quantitative research, with data collection techniques through: Observation, Interview, and Questionnaire/Questionnaire. Data analysis techniques: Simple Linear Regression Test, Hypothesis Test (t test) and Determination Test (R Square test). From the results of the analysis that the researchers did, it can be concluded that the variable "Employee Performance (Y) has a positive influence on the variable "Consumer Satisfaction" (X) where in a simple linear regression test it is found that every additional unit of Employee Performance Variable will increase satisfaction. Consumers are 0.441 or 44.1%, and the t test shows that the influence of employee performance on customer satisfaction at Hotel Setia Puruk Cahu Murung Raya is very significant where the significant value is 0.001 which means Ho is rejected and Ha is accepted, then the influence of employee performance is also classified as high on consumer satisfaction, which is equal to 0.614 or 61.4%.